'Exceedingly Obnoxious to others in the Trade': Carlisle Bookseller, Printer and Publisher Charles Thurnam (1796–1852). (2nd January 2021) - Collinge, Peter
Abstract : Early-nineteenth century traders, manufacturers and retailers are often depicted as inhabiting a world where approval, trust and reputation mattered. Positive engagements with customers, fellow business-people and with the wider community were all, apparently, important. This has been made most obvious in the literature in relation to clients whereby shop-keepers eager to please an increasingly affluent population, offered liberal terms to encourage repeat business. Entrants to the market place, keen to forge new connections with peers, drew on established links to enhance their own fledgling businesses. Publicised via newspapers, they promoted their integrative rather than disruptive appearance. The career of Carlisle printer and publisher Charles Thurnam questions this narrative. Intermingled with his civic engagement, Thurnam's outbursts of violence and aggression, threatening behaviour, legal entanglements and witness intimidation reveal an approach seemingly at odds with the notion of a 'polite and commercial' people.